A network of trans-cortical capillaries as mainstay for blood circulation in long bones. Issue 2 (February 2019) - Grüneboom, Anika; Hawwari, Ibrahim; Weidner, Daniela; Weidner, Daniela; Müller, Sylvia
No abstract available